Hetero-carbolong chemistry: experimental and theoretical studies of diaza-metallapentalenes. Issue 28 (20th March 2023) - Chu, Zhenwei; Li, Jinhua; Hua, Yuhui; Luo, Ming; Chen, Dafa; Xia, Haiping
Abstract : Treatment of azo compounds with an η 2 -alkyne-coordinated metallacycle via alkyne-azo coupling followed by aromatization efficiently afforded the first diaza-metallapentalenes. Abstract : Four diaza-osmapentalenes were prepared by two-step reactions, through the treatment of an alkyne-coordinated osmium complex with azo compounds, followed by the addition of AgSbF6 /CO. Their aromaticity was confirmed by crystal parameters, NMR spectra and theoretical calculations. These complexes are the first diaza-metallapentalenes representing a new class of metallaaromatics.